Maternal Bonding in Early Infancy Predicts Childrens' Social Competences in Preschool Age - Joas, Jens; Möhler, Eva (Frontiers in Psychiatry, 2021)
1 Abstract Background There are many studies on mother-child-bonding with little theoretical doubt that better bonding can have a positive effect on further social development. However, there is hardly any empirical evidence. In particular, there is a lack prospective longitudinal studies. Methods As part of a longitudinal study, bonding was assessed in a community sample of 97 healthy mothers using the Postpartum Bonding Questionnaire (PBQ) six weeks after birth of their child. Social competencies in the offspring were assessed using the Self- and Other-oriented Social Competencies (SOCOMP) at 5.5 years of age. A potential correlation between bonding and social competencies was tested using Spearman Rank Correlation. Results Retention rate over 5.5 years was 77.23%. Lower Maternal Bonding Impairment Scores 6 weeks postnatally were positively related to childrens’ social competences at 5.5 years of age. Conclusion The present data confirm the theoretically assumed positive and long-term influence of bonding on social skills and provide further evidence of the importance of parent child bonding for the whole development in general. This result should give reason to further investigate this relationship in depth, causally and at later points in time.